Revealed preferences over risk and uncertainty - Matthew Polisson; John K.-H. Quah; Ludovic Renou (Queen Mary University of London, School of Economics and Finance, 2017)
We develop a nonparametric procedure, called the lattice method, for testing the consistency of contingent consumption data with a broad class of models of choice under risk and under uncertainty. Our method allows for risk loving and elation seeking behavior and can be used to calculate, via Afriat's efficiency index, the magnitude of violations from a particular model of choice. We evaluate the performance of different models (including expected utility, disappointment aversion, rank dependent utility, mean-variance utility, and stochastically monotone utility) in the data collected by Choi et al. (2007), in terms of pass rates, power, and predictive success.
Keywords: C14; C60; D11; D12; D81; 330; expected utility; rank dependent utility; disappointment aversion; Bronars power; predictive success; generalized axiom of revealed preference; first order stochastic dominance; mean-variance utility; Afriat's efficiency index